Drug Allergy Profile From a National Drug Allergy Registry - Al-Ahmad, Mona; Edin, Jusufovic; Musa, Fardous; Rodriguez-Bouza, Tito (Frontiers in Pharmacology, 2021)
Background: Drug hypersensitivity reactions (DHRs) are among the most frequent reasons for consultation in allergy departments, and are becoming more common due to increasing prevalence and case complexity. Objective: To describe the most common drugs associated with clinical reactions, diagnostic methods used and outcomes of allergic evaluations, of a national drug allergy registry over a 12-year period. Methods: An observational, prospective, patient’s data registry-based study was conducted to analyze all referrals to the drug allergy outpatient clinics at Al-Rashed Allergy Centre, Kuwait, between 2007 and 2019. Demographics, description of DHRs, results of allergy tests to potential causative medications, were reviewed. Diagnostic methods were focused mainly on skin tests (ST) and drug provocation test (DPT), when indicated. Results: We evaluated 1553 patients with reported DHRs. The mean age of the population was 41.52 ± 16.93 years and the study population consisted of 36.3% males. Hypersensitivity was finally confirmed in 897 (57.8%) of patients, and in 656 (42.2%) patients the diagnosis was not confirmed. Antibiotics contributed to 36.2% of all confirmed drug allergies (β-lactam antibiotics (BLs) constituted 63.7% among all antibiotics and 23% among all drugs), followed by anti-inflammatory and analgesics 34.9%, anesthetics 1.4%, and radiocontrast media (RCM) 0.2%. The vast majority of reactions were immediate 93.2%. The most common presenting symptoms among confirmed patients were urticaria 56.1%, angioedema 47.6%, respiratory symptoms 46.7%, and erythema 46.3%. Symptoms of anaphylaxis/anaphylactic shock were reported by 378 patients (24.3%), and anaphylaxis represented 42.1% of all confirmed reactions. The most common method of diagnosis was a positive clinical history (59.9% in BLs, 96.31% in nonsteroidal anti-inflammatory drugs (NSAIDS), and 100% in RCM). A positive skin test was obtained in 28% of patients with reported BLs allergy, while those diagnosed by a positive DPT were 12%. Conclusions: In both confirmed and not confirmed, BLs are the most frequently involved DHRs which are mainly immediate, and the most common presenting symptoms were urticaria, angioedema and respiratory symptoms. Diagnosis was confirmed mainly by a positive clinical history and when indicated, by positive ST or a DPT.